Ligand density dramatically affects integrin αIIbβ3-mediated platelet signaling and spreading - Jiroušková, Markéta (American Society of Hematology, 2007)
The impact of ligand density on integrin-mediated cell adhesion and outside-in signaling is not well understood. Using total internal reflection fluorescent microscopy, conformation-specific antibodies, and Ca(2+) flux measurements, we found that the surface density of fibrinogen affects αIIbβ3-mediated platelet signaling, adhesion, and spreading. Adhesion to fibrinogen immobilized at low density leads to rapid increases in cytosolic Ca(2+) and sequential formation of filopodia and lamellipodia. In contrast, adhesion to high-density fibrinogen results in transient or no increases in Ca(2+) and simultaneous formation of filopodia and lamellipodia. αIIbβ3 receptors at the basal surface of platelets engage fibrinogen in a ringlike pattern at the cell edges under both conditions. This engagement is, however, more dynamic and easily reversed on high-density fibrinogen. Src and Rac activity and actin polymerization are important for adhesion to low-density fibrinogen, whereas PKC/PI3 kinases contribute to platelet spreading on high-density fibrinogen. We conclude that 2 fundamentally different signaling mechanisms can be initiated by a single integrin receptor interacting with the same ligand when it is immobilized at different densities.